Wisdom can be taught: A proof-of-concept study for fostering wisdom in the classroom. (December 2018) - Bruya, Brian; Ardelt, Monika
Abstract: We undertook a short-term longitudinal study to test whether a set of methods common to current theories of wisdom transmission can foster wisdom in students in a measurable way. The three-dimensional wisdom scale (3D-WS) was administered to 131 students in five wisdom-promoting introductory philosophy courses and 176 students in seven introductory philosophy and psychology control courses at the beginning and end of the semester. The experimental group was divided in two ("Wisdom 1" and "Wisdom 2"), and each was taught a distinct curriculum consistent with theories of wisdom education. Results of repeated measures MANOVA showed that over the course of the semester average 3D-WS scores decreased in the control classes, stayed the same in the Wisdom 1 classes, and increased in the Wisdom 2 classes. To our knowledge, this is the first time that a wisdom curriculum has been demonstrated to increase wisdom in a traditional higher education setting. Graphical abstract: Image 1 Highlights: Wisdom can be conceived as a strength to be cultivated. Prior studies measuring wisdom growth in the classroom have produced null results. Methods in the literature for fostering wisdom can be applied in the classroom. Declining scores in control groups show that a null result can still mean progress. One experimental group showed a null result and one showed an increase in wisdom.